Selective list of the issues of Catalogue of the VIR Global Collection on fruit, berry, nut, subtropical and ornamental crops, and grapes for 1961–2021 - article Editorial (Труды по прикладной ботанике, генетике и селекции)
Since 1961, VIR has been publishing the series Catalogue of the VIR Global Collection, which had the original name Catalogue–Directory of the VIR Global Collection. Since 2018, the edition notice for each issue and the abstract have been presented concurrently in Russian and English. The name of the series in English is Catalogue of the VIR Global Collection.